Pengembangan Teknik Dasar Menggunakan Video Tutorial Pada Atlet Pelajar Ekstrakurikuler Olahraga Gulat - Sabaruddin Yunis Bangun; Gery Ginting (Musamus Journal of Physical Education and Sport (MJPES), 2023)
The purpose of this study was to develop basic techniques using video tutorials for extracurricular student athletes in wrestling. The method in this study uses research and development (R&D). The population in this study were extracurricular student athletes in wrestling, a sample of 24 people, 10 samples were carried out in product trials and 14 samples were carried out in use trials. Data collection techniques using questionnaires or questionnaires. Data analysis technique using quantitative data analysis percentage and Likert scale. The results of the study were: From the results of the sports material validator it was found that the overall percentage was 81% with a "very decent" percentage. Media expert validator results with an overall percentage of 80% "very feasible" description. The results of the trial product percentage are 82% with the description "Very Eligible". The results of the usage trial with a percentage of 87% are in the "very feasible" category. The conclusion of this research is that the development of basic techniques using video tutorials for extracurricular student athletes in wrestling is very good and effective to implement